ALKBH5‐mediated m6A demethylation of TIRAP mRNA promotes radiation‐induced liver fibrosis and decreases radiosensitivity of hepatocellular carcinoma. Issue 2 (15th February 2023) - Chen, Yuhan; Zhou, Peitao; Deng, Yixun; Cai, Xinni; Sun, Mingrui; Sun, Yining; Wu, Dehua
Abstract: Background: Radiation‐induced hepatic stellate cell (HSC) activation promotes radiation‐induced liver fibrosis (RILF), a complication for hepatocellular carcinoma (HCC) radiotherapy. The demethylase alpha‐ketoglutarate‐dependent dioxygenase alkB homolog 5 (ALKBH5) decreases N6‐methyladenylate methylation (m 6 A) modification of RNA, while its role in regulating RILF pathogenesis and HCC radiosensitivity remains unknown. Methods: Methylated RNA immunoprecipitation sequencing (MeRIP‐seq) and RNA‐sequencing (RNA‐seq) were used to screen target genes regulated by ALKBH5. HSC with altered ALKBH5 expression was used to assess irradiation‐induced HSC activation and the effect of HSC on recruitment and polarisation of monocytes. Key cytokines in medium from irradiated HSC‐educated monocytes were identified by cytokine array detection. The effects of blocking ALKBH5 and key cytokines on RILF and HCC radiosensitivity were also evaluated. Results: Radiation‐induced ALKBH5 expression in HSC mediated m 6 A demethylation of toll‐interleukin 1 receptor domain containing adaptor protein (TIRAP) mRNA and activated its downstream NF‐κB and JNK/Smad2 pathways to promote HSC activation. Additionally, ALKBH5 regulated CCL5 secretion by irradiated HSC to promote monocyte recruitment and M2 macrophage polarisation. Notably, polarised monocytes secreted CCL20 to up‐regulate ALKBH5 expression in HSC, and reduce HCC radiosensitivity by activating ALKBH5/TIRAP axis in HCC cells. ALKBH5 knockdown‐combined CCR6 (CCL20 receptor) inhibitor significantly alleviated RILF and improved HCC radiosensitivity in mice. HCC patients with high ALKBH5 and TIRAP expression were prone to radiation‐induced liver injury and poor tumour response to radiotherapy. Conclusions: Collectively, irradiation up‐regulates ALKBH5 in HSC to mediate monocyte recruitment and M2 polarisation and form positive feedback to promote RILF and reduce HCC radiosensitivity. The dual roles of ALKBH5 as a microenvironmental regulator and radiosensitisation target provide new ideas for RILF prevention and radiosensitisation of HCC. Abstract : ALKBH5‐mediated TIRAP mRNA m 6 A demethylation promotes irradiated HSC activation ALKBH5 regulates the CCL5‐CCR5 axis to promote monocyte recruitment and M2 polarisation Irradiated HSC educated monocyte promotes HSC activation and reduces HCC radiosensitivity by CCL20 secretion Blocking ALKBH5‐CCR6 axis alleviates radiation‐induced liver fibrosis and improves HCC radiosensitivity